Pengukuran Kinerja Keuangan PT. United Tractors Tbk Dengan Pendekatan Metode Economic Value Added (EVA) - Tutut Puji Rahmawati (EKONOMIA, 2020)
Tractors Tbk With a Method Approach Economic Value Added (EVA), under the guidance of Mrs. Elfreda Aplonia Lau as the supervisor lecturer I and Mr. Murfat Effendi as supervisor II.Financial performance measurement is a formal effort to evaluate the efficiency and effectiveness of a company in generating certain profit and cash positions as a means or indicator in order to improve the company's operational activities. The basic theory used in this study is management accounting which focuses on the financial performance of PT. United Tractors Tbk with the analytical tool used is Economic Value Added EVA) and data collection techniques are library studies (library research).The results of the study, in 2014 the value of Economic Value Added (EVA) was Rp. 1,311,332,120,000, then in 2015 it decreased to Rp. 620,683,300,000 and in 2016 the value of Economic Value Added (EVA) experienced a decline again so that it was negative in the amount of Rp. (30,947,394,900,000). In 2017 the value of Economic Value Added (EVA) increased to Rp. 2,823,624,210,000. The researcher concluded that in general the company has been able to create economic value added for shareholders, even though the company experienced a decline and an increase in the value of Economic Value Added (EVA) created.